The Missing Link: Teacher Learning for Diversity in an Area-based Initiative in Portugal - Alves, Ines (2020)
As an attempt to promote educational success in socio-economically disadvantaged contexts, area-based initiatives are often launched in Europe, such as the programme Territórios Educativos de ntervenção Prioritária in Portugal. Given the importance of teaching quality to enhance student learning and considerable student diversity in the schools included in this initiative, this article explores opportunities for teacher learning for diversity within the programme. Documentary analysis was conducted on 188 school documents from 95 school clusters in the programme. The following research questions were asked: Does the programme promote teacher learning? In what ways is teacher learning promoted? Does teacher learning address diversity? The findings suggest that some interventions provide the possibility of teacher learning, such as the processes of learning together, pedagogical supervision, reflection, and attending professional development courses. However, diversity seemed to be largely missing from these initiatives. Furthermore, two cornerstones of teacher learning for diversity were absent: teachers’ critical reflection on students’ inclusion/exclusion; and learning from/with students, families, and communities. Additionally, most professional development opportunities were organised around and measured by students’ academic results, thus positioning teacher learning as instrumental in raising school success, rather than a core of transforming education for diversity. These results call for policies within the Territórios Educativos de Intervenção Prioritária programme to include teacher learning that engages with and fosters critical thinking around diversity and to involve communities’ and students’ voices in order to truly tackle social exclusion. The findings can contribute to the debate on the approach to diversity in area-based initiatives in Europe.